Wilding the tame - Slater, Kaie Lee (Nanyang Technological University, 2020)
Pablo Picasso once said, “in art 2 plus 2 can equal anything except for 4”. Likewise, the purpose of this research study is to investigate through the medium of product design, how concepts can equal anything but what their presumed purpose is. The concept of ‘absurdity’ in design is something that is often overlooked. Users tend to take products for granted, placing ‘function’ on a pedestal above all other elements. In a way, this limits a sense of excitement, wonder and the ‘play’ which may otherwise result between products and users. Studying how the use of absurdist comedy could be facilitated by product development, could enable a greater sense of engagement between users. In doing so, a variety of comedic material ranging from work by standup comedians, mockumentaries, texts and existing products will be explored, in order to find the right assimilation of the two fields of comedy and design. The portrayal of concepts should illicit a sense of inquisitiveness amongst viewers. An exploration of videography showcasing the absurdist concepts has been explored. Through a video format, concepts which are one-off have the chance to be circulated virally for a larger demographic of audiences to appreciate, seek comedic entertainment, and resonate with.This project aims to blur the fine line between art and design; the inventions explored through this study are wild, certainly strange and anything but ordinary.